ISLAMIC CULTURE DI ERA REVOLUSI INDUSTRI 4.0 : (TINJAUAN FILSAFAT TEKNOLOGI ANDREW FEENBERG) - Harisman, Harisman (Fakultas Ushuludin Adab dan Humaniora Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri, 2023)
Technological developments in the era of the industrial revolution 4.0 have changed the media used in developing Islamic culture. This paper tries to describe the development of Islamic culture to date. Various problems regarding developing technology raise questions regarding its use. The point of view that is widely used in viewing technology has not been able to represent the rationality of the technology itself. A rational reading of today's technology is possible to refer to the contemporary philosophy of Andrew Feenberg who has different views with his predecessors. The author uses a type of library research research with a qualitative approach. The analysis uses the viewpoint of Andrew Feenberg's technological rationality philosophy. As a result, the current technology makes access to Islamic cultural performances easier. One can watch a cultural performance anywhere and anytime and the spread of information and knowledge related to Islamic culture.